Astragaloside Ⅳ reduces renal vascular endothelial injury in uremic rat model - ZHU Wen-sheng, ZHENG Zhong-yu, LI Xiao-xia, DENG Jian-nan, ZHANG Ji-chun (Jichu yixue yu linchuang, 2021)
Objective To investigate the protective effect of astragaloside Ⅳ on vascular endothelium of uremic rat model by regulating nuclear factor-E2-related factor2 (Nrf2)/hemeoxygenase1 (HO-1) signaling pathway. Methods SD rats were randomly divided into sham operation group, model group, low- (100 mg/kg), high- (200 mg/kg) dose astragaloside Ⅳ groups, Nrf2 inhibitor group (2 mg/kg) and high-dose astragaloside Ⅳ+Nrf2 inhibitor(200 mg/kg+2 mg/kg) group, with 12 rats in each after the performance of intraperitoneal,the renal function index like serum creatinine (Scr), urea nitrogen (BUN), β2-microglobulin (β2-MG)and interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α) were detected by ELISA method, the pathological changes of renal vascular structure were observed by electron microscopy; Reactive oxygen species (ROS) were detected by immuno-fluorescence technology; the expression of CD31 and Nrf2 in renal tissue was detected by immuno-fluorescence co-localization; the expression of HO-1 and endothelial nitric oxide (eNOS) in renal tissue were detected by immuno-histochemistry; the expression of angiopoietin-like protein 6(ANGPTL6) and monocyte chemoattractant protein-1 (MCP-1) were detected by Western blot. Results Compared with those in the sham operation group, the erythrocyte aggregation, endothelial cell swelling and enlargement, lumen stenosis and compression in peri-tubular capillaries were serious in model group, the secretion of toxins such as Scr, BUN and β2-MG in serum, the levels of TNF-α and IL-6, renal tissue ROS(P＜0.05), positive expression of renal vascular tissue HO-1 and eNOS, the positive co-expression of CD31 and Nrf2, protein expression levels of ANGPTL6 and MCP-1 in renal tissue were increased (P＜0.05). Compared with those in the model group, the erythrocyte aggregation in peri-tubular capillary lumen, the swelling and enlargement of endothelial cells were alleviated in the low- and high-dose astragaloside Ⅳ groups, the levels of serum toxin and inflammation, renal tissue ROS, the expression of ANGPTL6, MCP-1, and eNOS was decreased (P＜0.05), and the expression of HO-1, co-expression of CD31 and Nrf2 in renal vascular tissues were increased (P＜0.05); the erythrocyte aggregation in peri-tubular capillary lumen, the swelling and enlargement of endothelial cells were further aggravated in Nrf2 inhibitor group, and the change trends of the above indexes were opposite to those in the astragaloside Ⅳ groups(P＜0.05). Conclusions Astragaloside Ⅳ may alleviate renal vascular endothelial injury in uremic rat model by promoting the activation of anti-inflammatory and anti-oxidant pathways mediated by the Nrf2/HO-1 pathway.